2020
DOI: 10.14202/vetworld.2020.1798-1806
|View full text |Cite
|
Sign up to set email alerts
|

Anti-feline immunodeficiency virus reverse transcriptase properties of some medicinal and edible mushrooms

Abstract: Background and Aim: Feline immunodeficiency virus (FIV) causes AIDS-like symptoms in domestic and wild cats. Treatment of infected cats has been performed using human anti-HIV drugs, which showed some limitations. This study aimed to determine the anti-FIV potential of some mushrooms. Materials and Methods: A total of 17 medicinal and edible mushrooms were screened to find their inhibitory effect against FIV reverse transcriptase (FIV-RT). Three solvents, water, ethanol, and hexane, were used to prepare crude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…This finding is consistent with a report, which stated that FeLV-infected cats are more likely to have low total protein, albumin, and globulin levels than non-infected cats [31]. Other studies reported that the BUN, creatinine, and serum ALT levels were significantly lower in FeLV-infected cats than in non-infected cats [36,37]. Although the present study showed no statistically significant association between infected and control cats concerning these three values, the BUN and creatinine levels were higher in cats infected with FeLV than in those infected with FIV.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with a report, which stated that FeLV-infected cats are more likely to have low total protein, albumin, and globulin levels than non-infected cats [31]. Other studies reported that the BUN, creatinine, and serum ALT levels were significantly lower in FeLV-infected cats than in non-infected cats [36,37]. Although the present study showed no statistically significant association between infected and control cats concerning these three values, the BUN and creatinine levels were higher in cats infected with FeLV than in those infected with FIV.…”
Section: Discussionsupporting
confidence: 92%
“…Determination of IC 50 value was performed according to the methods of Silprasit et al (2011) , which have been used in a number of researches ( Bahare et al, 2015 , Seetaha et al, 2020 ). Briefly, the 6–14 concentrations of two-fold serial dilution of the concentrated mushroom crude extract were prepared, and were then used as inhibitors in the assay.…”
Section: Methodsmentioning
confidence: 99%
“…For IC 50 calculations, the different concentrations of focused compounds and drug standards around 10 concentrations were performed to calculate the IC 50 values as previously described (Seetaha et al, 2020;Choengpanya et al, 2021). The reaction was started by adding 2 μL of focused compounds in each concentration into 96-well black plate.…”
Section: Determination Of Ic 50mentioning
confidence: 99%